Legal Protection for Franchisees Due to Unauthorized Franchise Agreements - Gultom, Ricky Ignatius Sadana; Urbaniasi, Urbaniasi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study analyzes legal protection for franchisees in unauthorized franchise agreements. The research method involves analysis of legal documents, literature studies, and a normative approach to the relevant legal framework. The results show that the franchisee has the option of cancellation of the contract, compensation, termination of unlawful activities, and recovery of rights that are not respected. Challenges in providing effective legal protection include regulatory weaknesses, cost and time of legal proceedings, and the power imbalance between franchisees and franchisors. This research has implications for increasing awareness, legal protection, and policies that encourage fair and stable business practices in the franchise industry.